2008
DOI: 10.3892/mmr_00000072
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified siRNA directed against the KDR gene inhibits the proliferation of breast cancer cells

Abstract: Abstract. Vascular endothelial growth factor receptor-2 or kinase insert domain-containing receptor (VEGFR2/KDR) is secreted by most solid tumors, including breast cancer, and is an important mediator of angiogenesis. To observe the effects of KDR gene expression on cell proliferation and the cell cycle in MCF-7 cells in vitro and in vivo, we used chemically modified siRNA directed against KDR. The results revealed that chemically modified siRNA transfection of the KDR gene effectively inhibited the proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…In accordance with our previous results showing that KDR-siRNA markedly decreased KDR gene expression and suppressed tumor growth in the xenograft model [13], using the siRNA-targeting KDR gene, we were able to silence the expression of KDR at the protein and mRNA levels. However, the molecular mechanisms underlying the anti-cancer effects of KDR-siRNA are not clearly understood.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In accordance with our previous results showing that KDR-siRNA markedly decreased KDR gene expression and suppressed tumor growth in the xenograft model [13], using the siRNA-targeting KDR gene, we were able to silence the expression of KDR at the protein and mRNA levels. However, the molecular mechanisms underlying the anti-cancer effects of KDR-siRNA are not clearly understood.…”
Section: Discussionsupporting
confidence: 77%
“…It provides us with an effective and simple method to specifically downregulate target genes [12]. We previously showed that KDR-siRNA suppressed tumor growth in a xenograft model [13], suggesting that KDR-siRNA might be an effective approach for the treatment of breast cancer. Apoptosis, also known as programmed cell death, is involved in the normal development of multicellular organisms and homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF/VEGFR-2 signaling system enhances ovarian cancer cell proliferation and survival [10][11][12]. Moreover, experiments on cancer cell lines proved that suppression of VEGFR-2 expression with siRNA inhibits proliferation of human breast cancer cells, and suppresses tumor growth in mice xenograft model [18]. Furthermore, recent studies showed that therapies with anti-VEGF antibody bevacizumab [19] or oral tyrosine kinase inhibitors targeting receptors for pro-angiogenic growth factors, including VEGFR-2 [20][21][22], reduce tumor growth, angiogenesis, ascites production, and improve survival in murine models of EOC.…”
Section: Variablementioning
confidence: 98%
“…The KDR gene is specifically expressed in certain tumor and vascular endothelial cells; therefore the KDR promoter has been used to express target genes in certain tumors due to its tumor-specific expression (20)(21)(22). In the present study, we report a potential treatment modality for breast cancer.…”
Section: Discussionmentioning
confidence: 99%